Emotional distress and burnout at a fever clinic in China: Comparison between different periods of COVID-19 - Geng, Wenqi; Cao, Jinya; Hong, Xia; Jiang, Jing; Hu, Jiaojiao; Duan, Yanping; Wei, Jing (Frontiers in Psychiatry, 2023)
Background Frontline healthcare workers (FHWs) experienced psychological stress and heavy workload during COVID-19 pandemic. This study examined the psychological symptoms and occupational burnout of FHWs in a fever clinic during different periods of the pandemic. Methods A cross-sectional survey of FHWs in the fever clinic of a tertiary hospital was carried out during both the outbreak period and regular period of COVID-19. Psychological measurement instruments including Generalized Anxiety Disorder 7-item, the 9-Question Patient Health Questionnaire, the Maslach Burnout Inventory-Human Service Survey, and the General Self-Efficacy Scale were used to evaluate anxiety, depression, burnout, and self-efficacy, respectively. The correlation between clinical variables was explored. Results A total of 162 participants were involved in this study, including 118 FHWs during the outbreak period (Group 1) and 44 FHWs during the regular period (Group 2). Anxiety symptoms were more prevalent in Group 2 (x2 = 27.477) while depressive symptoms were significantly more prevalent in Group 1 (x2 = 69.538). Burnout rate was higher in Group 2 (x2 = 29.526). Self-efficacy was higher in Group 1 (t = 3.194). Burnout was positively correlated with anxiety symptoms (r2 = 0.424) and negatively correlated with self-efficacy (r2 = −0.312). Conclusion Anxiety, depressive symptoms and burnout were prevalent in FHWs during different periods of the COVID-19 pandemic. There is a tendency to be less depressed, but more anxious and burned out over time, although the severity of the pandemic is decreasing. Self-efficacy may be an important factor in protecting FHWs from occupational burnout. Support and intervention plans for FHWs should be made at the institutional level.